Certolizumab Pegol Efficacy Across Methotrexate Regimens: A Pre‐Specified Analysis of Two Phase III Trials. Issue 3 (March 2016) - Combe, Bernard; Furst, Daniel E.; Keystone, Edward C.; van der Heijde, Désirée; Luijtens, Kristel; Ionescu, Lucian; Goel, Niti; Emery, Paul
Abstract : Objective: Anti–tumor necrosis factor (anti‐TNF) agents are frequently used in combination with methotrexate (MTX) to treat rheumatoid arthritis (RA). We investigated the effect of a background MTX dose, in combination with anti‐TNF certolizumab pegol (CZP), on treatment efficacy and safety in RA patients. Methods: A pre‐specified subgroup analysis comparing 2 MTX dosage categories (<15 mg/week and ≥15 mg/week) was carried out using data pooled from phase III clinical trials, Rheumatoid Arthritis Prevention of Structural Damage 1 (RAPID 1) and RAPID 2, according to treatment group: CZP 200 mg, CZP 400 mg, or placebo, every 2 weeks. Inclusion criteria required MTX dosage ≥10 mg/week. Efficacy end points included week 24 American College of Rheumatology criteria for 20%, 50%, and 70% improvement (ACR20/50/70) responses analyzed by logistic regression, and changes from baseline in the Disease Activity Score in 28 joints using the erythrocyte sedimentation rate (DAS28‐ESR) and the modified Sharp/van der Heijde score (SHS) were analyzed by analysis of covariance. Incidence rates of treatment‐emergent adverse events (TEAEs) were categorized by baseline MTX dose. Post hoc sensitivity analysis investigated 3 MTX dose categories: ≤10 mg/week, >10 and ≤15 mg/week, and >15 mg/week. Results: A total of 638, 635, and 325 patients received CZP 200 mg, CZP 400 mg, and placebo, respectively. At week 24, treatment responses in both CZP groups were uninfluenced by baseline MTX dose category, and were superior to the placebo group for all investigated end points: ACR20/50/70, DAS28‐ESR, and SHS. TEAE incidence rates were higher in patients receiving MTX ≥15 mg/week for most TEAE types across treatment groups. Conclusion: CZP efficacy was not affected by background MTX dose category. It can be hypothesized that to minimize TEAEs, background MTX doses could be tailored to individual patient tolerance without affecting CZP efficacy.